Implementasi Kebijakan Tarif Angkutan Umum Di Provinsi Sulawesi Utara (Studi Kasus Di Trayek Manado-Langowan) - Lukow, Triksinia; Rares , Joyce J.; Kawung, Evelin J.R. (Sam Ratulangi University, 2023)
This study aims to determine how the implementation of the Public Transportation Tariff policy in North Sulawesi Province, especially on the Manado - Langowan route transportation. This research was conducted from March to May 2023. The method used in this research is descriptive qualitative method. Informants used in this study were taken using purposive sampling technique totaling 16 people. Data collection was carried out by observation, interviews and documentation. The research focused on aspects of policy content and policy environment. Data analysis is done by reducing data, presenting data and drawing conclusions. The results showed that the policy focused on the basis and purpose of implementation illustrated that the basis for implementing public transportation tariff policies in North Sulawesi Province without exception on the Manado-Langowan route was based on Governor's regulation Number 303 of 2022 where through the Governor's regulation it was issued intended to adjust city transportation rates in the province of economy class including for public vehicles and taxis. Implementation of public transport tariff policies in North Sulawesi Province for the Manado-Langowan route, the government plays a full role in setting tariffs where its implementation is supported by drivers and passengers as policy users.